Extensive screening of cyclopeptide toxins in mushrooms by ultra-high-performance liquid chromatography coupled with quadrupole-Orbitrap mass spectrometry. (1st November 2020) - Lei, Shan; Shi, Peiyu; Wu, Wenling; Xia, Bing; Fu, Xian; Wan, Yuping; Zhou, Yan
Highlights: Detection of trace cyclopeptide toxins in mushrooms by Q-Orbitrap MS. Non-target screening of cyclopeptide toxin analogues by DIA acquisition mode. Three α-amanitin analogues were screened in Amanita rimosa sample without standard. Two of α-amanitin analogues were tentatively identified as unknown compounds. Abstract: A non-target screening method of cyclopeptide toxins and their analogues in mushroom was developed, using ultra-high-performance liquid chromatography coupled with quadrupole Orbitrap mass spectrometry (UHPLC-Q-Orbitrap MS) followed by mass spectrometry databases retrieval and software tools analysis for the candidate analogues. Three cyclopeptide toxins in the toxic mushroom Amanita rimosa were firstly screened without standard, and two of them were unknown analogues which were tentatively identified by the accurate masses, isotopic patterns and characteristic fragments. A validated quantitative method was performed to rapidly quantify three major cyclopeptide toxins in the Amanita rimosa sample including α-manitin, β-amanitin and phalloidin, and their contents were detected to be 4.52 mg/kg, 2.37 mg/kg and 2.53 mg/kg, respectively. The developed method has good selectivity and sensitivity for rapid and comprehensive screening the cyclopeptide toxins and their analogues in mushrooms at trace levels. Successful non-target screening of trace cyclopeptide toxin analogues will guarantee the food safety in mushrooms consumption.